Comprehensive characterization of high surface area activated carbon prepared from olive pomace by KOH activation - Sirazi, Meltem; Aslan, Sibel (Taylor & Francis Inc, 2021)
The use of abundant and inexpensive biomaterials such as agricultural by-products/wastes in the production of activated carbon has attracted considerable attention in recent years. Olive pomace (OP) is a solid waste resulting after extracting oil from olives in the olive oil production processes. OP was used as a precursor for the preparation of activated carbon as it is low-cost and abundantly available. In the experimental study, OP was chemically activated at various impregnation ratios using KOH as an activating agent. The effects of impregnation ratio and activation temperature on textural and morphological structure, surface chemistry, and surface area of prepared activated carbons were investigated. The OP-based activated carbons were characterized by SEM-EDX, BET surface area, iodine number, FTIR, pH(pzc), and elemental analysis. The activated carbons prepared had a specific surface area from 385.481 m(2)/g to 2451.770 m(2)/g, micropore volume from 0.1440 cm(3)/g to 0.8670 cm(3)/g, and mesopore volume from 0.1108 cm(3)/g to 0.7540 cm(3)/g. The increase in both activation temperature and impregnation ratio resulted in a higher specific surface area and micropore volume. Activation temperature and impregnation ratio significantly influenced the characteristics and yield of activated carbon. Based on the results obtained by the characterization studies, we can suggest that the high surface area activated carbons can be produced from olive pomace by KOH activation.
Keywords: Olive pomace; activated carbon; carbonization; activation; potassium hydroxide impregnation; agricultural by-products